2022
DOI: 10.1039/d1ea00107h
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigator series: deposited particles and human lung lining fluid are dynamic, chemically-complex reservoirs leading to thirdhand smoke emissions and exposure

Abstract: Tobacco combustion products in deposited particles and bodily reservoirs enable persistent thirdhand smoke contamination and transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…Biomass burning SOA has been proposed to largely originate from the oxidation of understudied VOCs such as phenols or furans (Akherati et al., 2020; Bruns et al., 2016; Hatch et al., 2017). Furans are a major class of heterocyclic compounds in biomass burning emissions that are generated from pyrolysis of cellulose (Ciccioli et al., 2001; Gilman et al., 2015; Hatch et al., 2017; Mettler et al., 2012) and are prevalent in other environments (e.g., tobacco smoke and indoor air) (Sheu et al., 2021, 2022). This class of compounds is highly reactive with atmospheric oxidants and can produce high yields of carbonyls that can further react to form BrC in the presence of ammonium (Aschmann et al., 2014; De Haan et al., 2020; Decker et al., 2019; Gómez Alvarez et al., 2009; Jiang, Tsona, et al., 2019; Koss et al., 2018; Laskin et al., 2015; Lee et al., 2013; Updyke et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass burning SOA has been proposed to largely originate from the oxidation of understudied VOCs such as phenols or furans (Akherati et al., 2020; Bruns et al., 2016; Hatch et al., 2017). Furans are a major class of heterocyclic compounds in biomass burning emissions that are generated from pyrolysis of cellulose (Ciccioli et al., 2001; Gilman et al., 2015; Hatch et al., 2017; Mettler et al., 2012) and are prevalent in other environments (e.g., tobacco smoke and indoor air) (Sheu et al., 2021, 2022). This class of compounds is highly reactive with atmospheric oxidants and can produce high yields of carbonyls that can further react to form BrC in the presence of ammonium (Aschmann et al., 2014; De Haan et al., 2020; Decker et al., 2019; Gómez Alvarez et al., 2009; Jiang, Tsona, et al., 2019; Koss et al., 2018; Laskin et al., 2015; Lee et al., 2013; Updyke et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…and are prevalent in other environments (e.g., tobacco smoke and indoor air) (Sheu et al, 2021(Sheu et al, , 2022. This class of compounds is highly reactive with atmospheric oxidants and can produce high yields of carbonyls that can further react to form BrC in the presence of ammonium (Aschmann et al, 2014;De Haan et al, 2020;Decker et al, 2019;Gómez Alvarez et al, 2009;Jiang, Tsona, et al, 2019;Koss et al, 2018;Lee et al, 2013;Updyke et al, 2012).…”
mentioning
confidence: 99%
“…19 If the condensed phase is aqueous, it has been observed that Henry's Law can describe both uptake and off-gassing, for instance from simulated lung lining uid. 44 Therefore, the chemical composition of THS lms controls the supply of tobacco-related SVOCs to the gas phase over long periods of time in THS contaminated environments. 16,19,20,45 Chemical characterization of fresh cigarette smoke has been widely conducted and thoroughly documented.…”
Section: Introductionmentioning
confidence: 99%
“…The composition, viscosity, and porosity of the substrate material has been implicated in the partitioning behaviour of compounds found in THS. 44 In this study, we intend to show that exposure of surfaces to sidestream cigarette smoke can induce oxidation in surface films, altering their composition to produce various oxidation products, including hydroperoxides. A non-volatile antioxidant (tris(2-carboxyethyl)phosphine; TCEP) was used to demonstrate oxidative action of THS films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation